2020
DOI: 10.3390/atmos11040378
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and the Pattern of the Hot Spots of War in Ancient China

Abstract: Quantitative research on climate change and war hot spots throughout history is lacking. In this study, the spatial distribution and dynamic process of war hot spots under different climatic phases in imperial China (1–1911 CE) are revealed using Emerging Hot Spot Analysis (EHSA), based on the Global Moran’s Index for testing the degree of spatial autocorrelation or dependency. The results show that: (1) Battles were significantly clustered regardless of any climatic mode or war category. (2) Hot spots for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The cold and hot spots analysis is one of the commonly-used methods to explore the local spatial clustering distribution characteristics. This method could collect the Getis-Orid G * i index of each element by calculating the elements, so as to determine whether there is high-value clustering or low-value clustering as well as to identify its location [50,54]. Furthermore, Getis-Orid G * i is a commonly-used index to describe the regional cold and hot spots, thus reflecting the correlation degree of SFQ grade between different research areas.…”
Section: Spatial Cold and Hot Spots Analysis Methodsmentioning
confidence: 99%
“…The cold and hot spots analysis is one of the commonly-used methods to explore the local spatial clustering distribution characteristics. This method could collect the Getis-Orid G * i index of each element by calculating the elements, so as to determine whether there is high-value clustering or low-value clustering as well as to identify its location [50,54]. Furthermore, Getis-Orid G * i is a commonly-used index to describe the regional cold and hot spots, thus reflecting the correlation degree of SFQ grade between different research areas.…”
Section: Spatial Cold and Hot Spots Analysis Methodsmentioning
confidence: 99%
“…However, this nationwide precipitation reconstruction only illustrates three major wet/dry cycles (multicentennial scale) in history as precipitation varies asynchronously in China. Therefore, according to and Zhang et al (2020b), a 300-year Butterworth low-pass filter was used to retrieve the low-frequency signal, and the average of this sequence was calculated to facilitate comparisons, based on which three wet (WP, to avoid confusion with the abbreviation of "warm")-dry (D) cycles were divided (also, please see Table S2b in Online Resource for details). The imperial era from 5 to 1911 CE was thus considered as the study period for consistency.…”
Section: Datamentioning
confidence: 99%
“…Such "outliers" of war centers during cycle 5 (1206-1490 CE) may not be attributed to temperature change. In fact, as the national precipitation series reconstructed by and the related wet-dry cycles divided by Zhang et al (2020b) show, the stage D2 (1042-1262 CE) is basically dry; besides, the period around 1150-1250 CE is the driest century during the last 2000 years . Since W5 partly overlaps with this dry interval (1206-1262 CE), and Fang (1989) and Pei and Zhang (2014) have indicated that precipitation rather than temperature is more influential in determining southward nomadic migration and the subsequent conflicts between pastoralists and agriculturalists, the anomalous southward shift of war center in W5 could be explained to some extent.…”
Section: Other Factors Beyond Temperaturementioning
confidence: 99%
“…The common theme of the associated papers is to reveal the non-linear and complex relationship between climate change and the positive checks in historical China and pre-industrial Europe. Zhang et al [3] employ Emerging Hot Spot Analysis to examine war hot spots in China from 1-1911. They show that war hot spots were generally located in the Loess Plateau and the North China Plain during warm and wet periods, but in the Central Plain, the Jianghuai area, and the lower reaches of the Yangtze River during cold and dry periods.…”
Section: Historical Periodsmentioning
confidence: 99%